Assembly of petrol engine and conversion to LPG system / Tg. Mohd. Tg. Ab. Rahman, Yusoff Yaacob and Rasdi Deraman - Tg. Ab. Rahman, Tg. Mohd.; Yaacob, Yusoff; Deraman, Rasdi (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1985)
There are two separate frames made in this project. i. Frame for engine petrol. ii. Frame for L.P.G. system. All the dimensions for the frames are measured according to the engine and L.P.G. equipments sizes. The components of the frames are joint by using arc welding. The types of joint used is square butt-joint. (See Fig: 1.1a and 1.1b Page and ) 1.1.1. PROCEDURE FOR ARC WELDING i. The place to be welded must be clean and free from dust, paint or any other contaminants. ii. Set the voltage according to the thickness of the plate to be joint. iii. Set correct clearance between two plate to be joint.